A novel assessment technique for measuring ankle orientation and stiffness. Issue 12 (18th September 2015) - Zhang, Mingming; Davies, T. Claire; Nandakumar, Anoop; Quan Xie, Sheng
Abstract: The measurement of ankle orientation and stiffness can provide insight into improvements and allows for effective monitoring during a rehabilitation program. Existing assessment techniques have a variety of limitations. Dynamometer based methods rely on manual manipulation. The use of torque meter is usually for single degree-of-freedom (DOF) devices. This study proposes a novel ankle assessment technique that can be used for multiple DOFs devices working in both manual and automatic modes using the position sensor and the multi-axis load cell. As a preliminary evaluation, an assessment device for ankle dorsiflexion and plantarflexion was constructed. Nine subjects participated to evaluate the effectiveness of the assessment device in determining ankle orientation and stiffness. The measured ankle orientation was consistent with that from the NDI Polaris optical tracking system. The measured ankle torque and stiffness compared well with published data. The test–retest reliability was high with intraclass correlation coefficient (ICC2, 1 ) values greater than 0.846 and standard error of measurement (SEM) less than 1.38.